Exportac\~oes e desempenho das firmas: Uma revis\~ao bibliográfica - Bruno César Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This literature review aims to systematize the knowledge about the relationship between exports and firm performance, in developed countries, developing countries and in Brazil. Especially, this review pays particular attention to the learning-by-exporting hypothesis, that is, firms' performance improvements - in particular, in productivity - experienced after the entry into the international market. In general, the confirmation of the learning-by-exporting hypothesis, when present, tends to occur in the articles relating to developing countries and Brazil. One possible explanation is that firms in these countries tend to operate below the technological frontier; hence, they have more to gain from international trade, at least marginally. In short, this review shows that competitive firms become exporters, but not necessarily exporters become more competitive.
Keywords: F14; 330; learning-by-exporting; exports; firms; productivity